Effect of Parthenium weed manures on rhizosphere mycoflora of maize - U.P. Mogle, D.R. Chamle1, D.A. Dhale2 and (Current Botany, 2011)
The aim of the present investigation was to study the rhizosphere mycoflora of maize under the influence of Parthenium hysterophorus L. weed manures has been investigated. A total of 11 fungal species were isolated viz., Aspergillus niger, A. flavus, A. terrus, Aspergillus sp., Cladosporium fulvum, Fusarium oxysporum, Mucor sp., Penicillium notatum, Phytophthora infestans, Rhizopus stolonifer and Trichoderma viride. Among these, the genus Aspergillus was most predominant. The analysis of soil samples from treated plots showed that more frequent mycoflora due to the application of weed manures. The mycopopulation were greater in the CM amendment followed by VM, DM, GM and NPK as compared to CO treatment.